One-pot synthesis of a nitrogen and phosphorus-dual-doped carbon nanotube array as a highly effective electrocatalyst for the oxygen reduction reaction - Zhu, J.; Jiang, San Ping; Wang, R.; Shi, K.; Shen, P. (R S C Publications, 2014)
A nitrogen and phosphorus-dual-doped carbon nanotube (N, P-CNT) array has been successfully synthesized by a novel one-pot method, using an aminophosphonic acid resin as the N, P and C sources. The N, P-CNTs are open with large inner channels, allowing oxygen molecules to access a large number of catalytically active sites on the inner walls. The N, P-CNTs are not only comparable to Pt/C in electrocatalytic activity for the oxygen reduction reaction (ORR) in 0.1 M KOH, but are also highly stable and tolerant to methanol and CO poisoning. An onset potential of 0.95 V close to that of Pt/C and a well-defined limiting current plateau for the ORR are observed. Moreover, there is almost no visible current density decrease on N, P-CNTs after 5000 cycles.